2011
DOI: 10.1260/2041-4196.2.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Concrete Masonry Walls with Membrane Catcher Systems Subjected to Blast Loading

Abstract: This paper describes a methodology for analyzing the impulse pressure response of unreinforced concrete masonry walls that have been retrofitted with membranes that are not bonded to the masonry (catcher systems). Membrane catcher systems can be used to protect building occupants from secondary debris resulting from blast pressure, and the effectiveness of systems comprised of polymers, composites, geotextiles, and thin steel and aluminum sheets has been researched extensively over the past fifteen years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…One significant difference between the Moradi method (Moradi et al, 2008, 2011) and the Wiehle/UFC method is that the Moradi approach includes an axial force associated with load-bearing walls. The free-body diagram used by Moradi et al is shown in Figure 8.…”
Section: Review Of Static Resistance Definitionsmentioning
confidence: 99%
“…One significant difference between the Moradi method (Moradi et al, 2008, 2011) and the Wiehle/UFC method is that the Moradi approach includes an axial force associated with load-bearing walls. The free-body diagram used by Moradi et al is shown in Figure 8.…”
Section: Review Of Static Resistance Definitionsmentioning
confidence: 99%
“…Structural frames infilled with unreinforced concrete masonry unit walls are very common all over the world. CMU walls are frequently used in buildings because they offer a costeffective option and can satisfy many building requirements; however, they are extremely susceptible to blast pressure, resulting in wall collapse, fragmentation, and severe injury to occupants (Wu, Hao 2007;Moradi 2007;Hao, Tarasov 2008;Wang, Hao, Ding, Li 2009;Moradi, Dinan, Bewick, Davidson 2011;Bazhenov, Kibetz, Kruszka 2012). Consequently, there is a need to retrofit CMU walls to increase their resistance to blast loading.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…The bonded approach typically involves the application of a thin layer of a spray-on or trowel-on elastomer. The effectiveness of the bonded approach and the development of resistance functions has been presented previously (Davidson et al, 2004(Davidson et al, , 2005Moradi et al, 2008Moradi et al, , 2009Moradi et al, , 2011 and is not the focus of the present article. The unbonded method is often referred to as a "catcher system" since it simply acts as a barrier that catches the wall debris.…”
Section: Introductionmentioning
confidence: 99%